On the copper(ii) binding of asymmetrically functionalized tripodal peptides: solution equilibrium, structure, and enzyme mimicking. (5th February 2018) - Dancs, Ágnes; Selmeczi, Katalin; May, Nóra V.; Gajda, Tamás
Abstract : The increasing histidyl functionalisation of tren results in the fundamental impact on the structure, stability and catecholase activity of its copper(ii ) complexes. Abstract : Our aim is to combine the preorganized structure of tripodal scaffolds and the advantageous metal-binding ability of histidine subunits. To this end, recently we have studied the copper(ii ) complexes of the tris(l -histidyl)-functionalized tren derivative, tren3his. Here we report the copper(ii )-binding properties of the mono- and bis(l -histidyl)-functionalized tren ligands (tren1his (L 1 ) and tren2his (L 2 )), and thus explore the impact of increasing histidine 'density' on the copper(ii ) binding of these tripodal peptides. Our solution equilibrium study was supplemented by several (UV-vis, CD, ESR, and NMR) spectroscopic and MS methods. The mono-His derivativeL 1 forms only mononuclear complexes. Above pH 4, the tren-like subunit is the main binding site, which is supplemented by an imidazole coordination. In the case ofL 2, both mono- and dinuclear copper(ii ) species are formed. In the acidic–neutral pH range, the highly stable bis-histamine-type binding mode dominates in the equimolar solution, while at a higher pH amide coordinated complexes are present. The bis-histamine coordination in CuHL 2 creates a preorganized structure, which promotes the binding of a second metal at the tren-like binding site with {N −, N tert, N − } coordination in Cu2 H−1 L 2 /Cu2 H−2 L 2 . Only the dinuclear Cu2 H−2 L 2 complex was found to efficiently catalyze the oxidation of H2 DTBC. The kinetic data resulted in a very high k cat / K M ratio (4360 M −1 s −1 ), which is due to the exceptionally strong substrate-binding ability of the dinuclear complex. However, the oxidation of the substrate within this adduct, which is a common feature of catalytically active dicopper(ii ) complexes, does not occur in the absence of dioxygen. This finding implies that the role of dioxygen is the oxidation of the substrate activated by the dinuclear complex. We assume a Cu(ii )Cu(ii )–catecholate–Cu(ii )Cu(i )–semiquinone valence tautomer (VT) equilibrium. The semiquinone formed in small quantities reacts with dioxygen in a rate-determining step, which eventually results in DTBQ and H2 O2 products. The Cu(ii )–L 2 complexes also exhibit efficient superoxide dismutase-like activity, supporting the versatility of tripodal peptide complexes in redox enzyme mimicking.